Influence of Virtual Reality Illusions on Balance Performance and Immersive User Experience in Young Adults: A Within-Subject Experimental Study - Abayasiri, R Achintha M; Padilha Lanari Bo, Antonio; Dick, Taylor J M; Baghaei, Nilufar (JMIR serious games, 2025)
Rehabilitation interventions to improve standing balance are often tedious and complex, limiting user engagement and increasing the burden of the clinicians delivering them. Virtual reality (VR) has been incorporated into such practices as a solution and VR illusions have emerged as a method for perturbing balance within interventions. However, the influence of VR illusions on balance performance, such as center of pressure (CoP), and user experience metrics remain under explored. This study aimed to evaluate the impact of the VR illusions on standing balance and immersive user experience in young adults. Young healthy adults (N=15, aged 18-35 years) played a VR table tennis game while standing on a force plate and were provided with eight directional and magnitude-based VR illusions scaled according to participants' heights. VR illusions were generated by offsetting the position of the playing hand in VR and were provided through 8 trials for each participant. Each VR illusion was delivered throughout final 50 seconds of each 70-second trial. Absolute CoP displacements, directional tendency of CoP displacement, and game performance were analyzed to evaluate the impact of the VR illusions. Responses to the User Experience Questionnaire, Slater-Usoh-Steed Presence Questionnaire, NASA Task Load Index, and Virtual Reality Sickness Questionnaire were analyzed to assess the immersive user experience. Both the magnitude of VR illusion and changes in VR illusion direction led to significantly greater CoP displacements, with high illusion magnitudes, and anterior and posterior directional illusions associated with higher CoP displacements. Conversely, those illusion magnitudes and directions were associated with low game performance. The directional tendency of the CoP displacements varied across the illusion directions but showed a significant association with the illusion directions. Questionnaire responses showed that participants had moderate to high immersive user experience within the VR illusion paradigm. This study provides a novel approach for the future development of more effective VR-based balance rehabilitation interventions. The results provide inspiration for the development of future VR-based exergames that can perturbate CoP direction and magnitude. By adjusting the difficulty level through directional and magnitude changes in VR illusions, exergames could provide a personalized rehabilitation experience.